The Arab world unbound tapping into the power of 350 million consumers - Mahajan, Vijay, 1948-; Zehr, Dan.; ebrary, Inc. (San Francisco : Jossey-Bass, 2012)
"An expert's guide to exploring business opportunities in the burgeoning Arab marketplaceThis groundbreaking book reveals the myriad opportunities presented by the Arab World's market of 350 million consumers, who collectively wield the ninth-largest economy in the world. Based on the author's firsthand research, including hundreds of market visits and more than 600 interviews at companies doing business throughout the region, this book shows how globally interconnected and vibrant the Arab markets are. Through a rich blend of data and anecdotal observations, it chronicles how, by respecting the region's culture and religious norms, hundreds of local and multinational companies and entrepreneurs are creating successful businesses in this large and growing marketplace. Hundreds of interviews and illustrative examples peel away stereotypes about Arab consumers to reveal diverse, vibrant and entrepreneurial consumer markets Explains how multinational companies, such as Coca-Cola, Unilever, and Proctor & Gamble, and leading regional companies are working successfully in the Arab nations Shows how Arab entrepreneurs, both men and women, are shaping the regional and global marketplaces Vijay Mahajan, author of two previous award-winning books on emerging markets, is one of the world's most-cited researchers in the business and economics sector As the global marketplace continues to expand, this book offers anyone interested in investing in the Arab world an expert perspective on the boundless business opportunities"--
Machine generated contents note: Foreword Preface Introduction Part I Discovering the Arab World Chapter 1 Drinking Red Bull in Dahiye The Arab market is vibrant and globally interconnected Arab consumers control more spending power than you think The shadow economy Shades of India and China Arab wealth beyond the crude oil Arab wealth beyond the abaya Household spending in the Arab World Consumer brands in both Israel and the Arab countries Chicken fights: Local competition in the Arab market The global emergence of Arab brands A worldwide hub: The Arab world is globally connected The Arab world is neither CNN's nor Al Jazeera's Chapter 2 The Diversity of the Arab World No harm in haram Not all the consumers in Arab countries are Arab The diversity of Arab consumers Segmenting the Arab consumer markets Embracing the diverse habits of Arab consumers The language differences The market dominance of Saudi Arabia and the GCC Think regional, act local Chapter 3 Islam Matters: How the Five Pillars of Islam impact consumers in the Arab World The difference between culture and religion Why shahada matters Why salah matters Why sawm matters Why zakat matters Why hajj and umrah matter Islam in the everyday Part II Tapping the well of Arab consumers Chapter 4 The shabab: tapping the Arab youth market The shabab demographic dividend The shabab crave the best brands, wherever they come from The shabab generation is molding the consumer market The shabab generation is changing the Arab workforce The shabab and education The shabab and marriage Chapter 5 Tapping the Arab Middle Class The rise of the middle class is changing the Arab consumer markets Identifying the Arab middle class Tapping into Arabia Two Tapping into Arab consumer power at all levels Urbanization, modern trade and Arabia Two Arabia Two and the balance between tradition and modernity Chapter 6 Tapping into the Arab women market Arab women have money to spend Educated women are reshaping the Arab market The Arab woman as a consumer Inside and outside: The dual identities of Arab women Tapping into the Arab beauty market The Arab woman as wife and mother The veil doesn't hide the Arab woman's mind Arab women as business leaders Arab women are reshaping the region on their own terms Chapter 7 Tapping into the Arab technology market The spread of Internet use opens up new paths to consumers The rise of social media Tapping into Arab e-commerce Using technology to recapture a Golden Age On the go: The market for mobile phones Building the high-tech industry in Jordan The technological Arab spring Chapter 8 Tapping into the Arab media and entertainment market Television advertising in the Arab world Arab cinema and film Dancing in the desert: Music in the Arab world Art in the Arab world Books and bookstores The birth of an Arab superhero Chapter 9 Tapping into the Arab diaspora Linking the diaspora to the Arab world Remittances constitute a critical piece of many Arab economies Tapping into the Arab diaspora The Arab diaspora has made a name for itself Tapping into opportunities around the world You can go home again The diaspora is bringing different worlds together Part III Conclusion Rebranding the Arab World Yalla Arabia! Capturing the region's yalla energy with a new Arab brand Sustaining the yalla energy of family businesses Harvesting the yalla energy of Arab youth Fueling the yalla energy of Arab entrepreneurs Enabling a new yalla energy among disadvantaged Arabs Letting the yalla energy flow A call to action The richness of the past and the promise of the future Acknowledgments The Authors Index.
Includes index.
Electronic reproduction.
Keywords: Marketing -- Arab countries; International business enterprises -- Arab countries; Electronic books